Effect of withholding food versus feeding on creatinine, symmetric dimethylarginine, cholesterol, triglycerides, and other biochemical analytes in 100 healthy dogs. (14th February 2023) - Yi, Katarina C.; Heseltine, Johanna C.; Jeffery, Nicholas D.; Cook, Audrey K.; Nabity, Mary B.
Abstract: Background: Withholding food is often recommended before collection of blood for routine biochemical analysis in dogs despite a paucity of evidence to support this requirement. Objectives: To compare measurements of selected biochemical analytes collected before and after feeding in clinically healthy dogs. Animals: One hundred clinically healthy staff‐ and student‐owned dogs weighing ≥15 kg. Methods: Prospective observational study. Food was withheld from the dogs for 10‐26 hours. Preprandial serum was collected, and then dogs were fed their usual food at an amount equivalent to at least 2/3 resting energy requirement (RER). Selected serum analytes were measured at 2‐, 4‐, 6‐, and 8‐hours postprandially. The proportion of postprandial values that exceeded either the reported allowable total error (TEa), or for symmetric dimethylarginine (SDMA), the reference change value (RCV), was determined. As neither TEa nor RCV is available for lipase, comparison was made to the high end of the reference interval (RI). Results: The proportion of dogs with at least 1 postprandial measurement that exceeded the TEa or RCV was 92/100 for triglycerides, 66/100 for blood urea nitrogen (BUN), 46/100 for phosphorus, 17/100 for glucose, 9/100 for bilirubin, 5/100 for SDMA, 2/100 for creatinine, and 0/100 for cholesterol and albumin. Postprandial lipase never exceeded the RI in dogs with normal fasted lipase. Conclusions and Clinical Importance: Withholding food is generally not necessary before performing routine biochemical analysis in clinically healthy dogs. Withholding food might be helpful to limit variability in analytes impacted by feeding, such as triglycerides and phosphorus.